2015
DOI: 10.4236/ajps.2015.69141
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variation among Sorghum (<i>Sorghum bicolor</i> L. Moench) Landraces from Eritrea under Post-Flowering Drought Stress Conditions

Abstract: Sorghum (Sorghum bicolour (L.) Moench) grown under rain-fed conditions is usually affected by drought stress at different stages, resulting in reduced yield. The assessment of variation in morpho-physiological traits contributing towards drought tolerance at these stages is of vital importance. This study was conducted using a split plot design with three replications to evaluate 25 sorghum accessions at post flowering stage under well watered and drought stress conditions at Hamelmalo Agricultural College. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
18
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(31 citation statements)
references
References 25 publications
10
18
0
2
Order By: Relevance
“…Therefore, the breeders could get chance to select promising genotypes based on the phenotypic performance of these traits. Agreeing with the present study, high heritability estimates for overall agronomic aspect were reported by Abraha et al (2015). High heritability estimates for plant height was also reported by Tomar et al (2012), Godbharle et al (2010) and Bhagasara et al (2017) which is in accordance with the present findings.…”
Section: Degree Of Freedomsupporting
confidence: 93%
See 2 more Smart Citations
“…Therefore, the breeders could get chance to select promising genotypes based on the phenotypic performance of these traits. Agreeing with the present study, high heritability estimates for overall agronomic aspect were reported by Abraha et al (2015). High heritability estimates for plant height was also reported by Tomar et al (2012), Godbharle et al (2010) and Bhagasara et al (2017) which is in accordance with the present findings.…”
Section: Degree Of Freedomsupporting
confidence: 93%
“…The difference between PCV and GCV was maximum for grain yield followed by number of seeds per panicle, indicating that these traits are more influenced by the environment. The highest PCV and GCV value for plant height is in accordance with the report of Abraha et al (2015). Tomar et al (2012) and Godbharle et al (2010) also reported low PCV and GCV on days to 50% flowering and Warkad et al (2008) and Abraha et al (2015) also reported low PCV and GCV on days to maturity.…”
Section: Degree Of Freedomsupporting
confidence: 77%
See 1 more Smart Citation
“…GCV values were minimal for days to 50% maturity and days to 50% flowering and medium for plant height and finger length. The current diversity research on finger millet is in agreement with previously conducted researches, considering the quantitative traits of maize and sorghum [20], [21], [22]. For all considered characters, the overall PCV values were higher than their corresponding GCV values.…”
Section: Mean and Range Valuessupporting
confidence: 89%
“…Pemuliaan tanaman merupakan suatu upaya peningkatan kualitas dan kuantitas tanaman yang bertujuan untuk menghasilkan varietas yang lebih baik atau lebih unggul (Lubis et al, 2014). Beberapa peubah genetik yang dapat digunakan untuk menentukan apakah suatu peubah dapat dijadikan kriteria seleksi, diantaranya adalah ragam genetik, ragam fenotip, dan heritabilitas (Yunianti et al, 2010;Anas et al, 2015;Abraha et al, 2015). Jika ragam genetik suatu variabel tinggi maka nilai heritabiitas akan tinggi sehingga variabel tersebut bisa digunakan sebagai kriteria seleksi.…”
Section: Pendahuluanunclassified